(untitled) (Almanack, 2022)
This article compares the mechanisms of popular politicization in nineteenth-century France and Brazil, in light of the innovative approaches of Emmanuel Fureix, presented at Almanack’s forum on 26 August 2014, and published as an article in this issue. Fureix analyzes rites of protest in France from the 1820s to the 1840s and suggests that opposition funerals, political banquets, and charivaris were part of a process of predemocratic politicization. Although it is easy to identify similar practices in nineteenth-century Brazil, they did not lead to a more democratic or “modern” politics in the second half of the century.